Epidemiological characteristics, treatment, and outcomes of 586 cases of intussusception: a 4-year retrospective study in China - Zhang, Lianzhi; Chen, Xiaotong; Huang, Yajun; Wang, Guimei; Zhang, Zhongxi; Song, Zai (Frontiers in Pediatrics, 2024)
Objective This study aims to retrospectively analyze the epidemiological and clinical characteristics of acute intussusception in a tertiary-care pediatric hospital in China over 4 years and evaluate the effectiveness and recurrence of fluoroscopy-guided pneumatic reduction (FGPR) and ultrasound-guided hydrostatic reduction (UGHR). Methods This retrospective study was conducted from January 2019 to December 2022 involving children admitted and managed for acute intussusception in a tertiary-care pediatric hospital in China. The epidemiology, clinical features, and therapeutic effects were analyzed using IBM SPSS Statistics 20.0. Results The study included 401 boys (68.43%) and 185 girls (31.57%) aged from 2 months to 12 years. The most common symptoms reported were abdominal pain or paroxysmal crying (95.73%), vomiting (45.39%), and bloody stool (7.34%). Vomiting and bloody stool became atypical with increasing age (P < 0.001). The total success cases of reduction accounted for 563 cases (96.08%), and the recurrent cases accounted for 71 cases (12.12%). No significant difference was observed in the success or recurrence rates between FGPR and UGHR (P > 0.05). Abdominal pain was an independent protective factor for successful enema (P < 0.01, OR = 72.46), while bloody stool (P < 0.01, OR = 0.06) and older age were independent risk factors (P < 0.001, OR = 0.51). Of the 71 patients with recurrent intussusception, 29 were successfully reduced by enema, and the other 23 required surgical reduction. Twelve of the surgical cases were secondary intussusception, including three cases of Meckel's diverticulum, five cases of polyps, and four cases of non-Hodgkin lymphoma. Conclusion The epidemiological characteristics of children with intussusception in Xiamen showed peculiarity with a higher male-to-female ratio, older age at diagnosis, and no significant seasonality. Both FGPR and UGHR were effective and safe for intussusception, and surgical reduction was essential for patients with failed enema reduction.